Pencegahan Praktik Politik Uang di Masyarakat Desa Sangiang Kecamatan Pamarayan - Marlina, Lina; Asmawi, Muhammad; Anwar Mahmud, Toni; Untari, Aryanti Dwi (CV. Kurnia Grup, 2024)
The implementation of this community service activity is located in Sangiang Village, Beusi Pasir Village, RT. 009 RW 04 Pamarayan District, The service activity was carried out on Wednesday, August 31, 2023 at the Sangiang Village office, this activity was carried out with the involvement of the Sangiang Village community, Karang Taruna, and a team of 2023 KKM Students Group 20 and PPKn Lecturers at Banten Jaya University. This activity has the theme of Prevention of Money Political Practices in the Community of Sangiang Village, Pamarayan District, Prevention of Money Political Practices is expected to be able to become a forum for public awareness in efforts to Prevent Money Political Practices, The methods used in this service activity are Counseling and Socialization and Discussion. Counseling and Socialization began with the elaboration of legal rules regarding programs, objectives, sanctions, voter education and examples of problems that often occur in the community regarding the practice of money politics while the discussion began with brainstorming activities, lectures and questions and answers, and the final result is expected that the community can play an active role in preventing the practice of money politics in the community of Sangiang Village, Pamarayan District, so that the upcoming democratic party in 2024 will be colored by a sense of mutual support and sportsmanship in its implementation and the community in the future will also realize the important role of public concern for this matter to be able to build a just and prosperous Indonesian country.